The Influence of Total Quality Management and Reward System to Managerial Performance - Sudarmadi, Dedy; Satyawisudarini, Inne; Maulina, Rena (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
Managerial performance can be understood as a system that is important for the success of a business or non-business organization. The achievement of an organizational success is inseparable from the role of the manager. Aims to produce the final result in accordance with company goals. Integrated Quality Management and Reward System are factors that can affect managerial performance. The purpose of this study was to determine the effect of Integrated Quality Management and reward systems on managerial performance at PT. Raya Consult. This research was conducted using a survey method by distributing questionnaires to the population with statistical data processing using SEM-PLS The results of this study indicate that: (1) Total Quality Management has an effect on managerial performance, (2) the reward system has an effect on managerial performance.